Cluster Analysis of Interregional Migration in Turkey - Akın, Darçın; Dökmeci, Vedia (American Society of Civil Engineers (ASCE), 2015)
AbstractDuring the past several decades, many studies illustrated the importance of socioeconomic factors on interregional migration in different countries. Interregional migration has had an immense impact on Turkey’s population dynamics after the 1950s. This study aims at investigating the patterns of interregional migration in Turkey during the period of 2008 to 2010 using a hierarchical cluster analysis. First, the paper gives background information about interregional migration by providing the ratios of immigration and emigration with respect to the population and the characteristics of the regions between 2007 and 2010. Second, interregional immigration and emigration flows are investigated by the use of a hierarchical clustering analysis with different linkage techniques, e.g., single, complete, average, and others, which determine how the distance between two clusters should be defined to represent actual partitioning. Then, the best partitioning of the regions is selected based on a popular inte...